Employer Attitudes towards Refugee Immigrants - Per Lundborg; Per Skedinger (Research Institute of Industrial Economics (IFN), 2014)
We present a large survey with responses from Swedish firms on their attitudes towards refugees, regarding hiring, job performance, wage setting and discrimination. Generally, firms report positive experiences of having refugees as employees, but we also document a great deal of heterogeneity in attitudes. Firms that ceased to have refugees on the payroll are less satisfied with their job performance, which seems related to poor language skills and less screening of refugees but not to discrimination of them by staff or customers. While most firms agree with statements that wage cuts negatively affect worker cohesion, effort or the quality of applicants, employers who consider such cuts as employment-enhancing tend to not agree.
Keywords: J15; J23; J71; 330; Refugee immigrants; Labour demand; Discrimination